Evaluating and Refining the Conceptual Model Used in the Study of Health and Activity in Preschool Environments (SHAPES) Intervention. (December 2017) - Saunders, Ruth P.; Pfeiffer, Karin; Brown, William H.; Howie, Erin K.; Dowda, Marsha; O'Neill, Jennifer R.; McIver, Kerry; Pate, Russell R.
This study investigated the utility of the Study of Health and Activity in Preschool Environments (SHAPES) conceptual model, which targeted physical activity (PA) behavior in preschool children, by examining the relationship between implementation monitoring data and child PA during the school day. We monitored implementation completeness and fidelity based on multiple elements identified in the conceptual model. Comparing high-implementing, low-implementing, and control groups revealed no association between implementation and outcomes. We performed post hoc analyses, using process data, to refine our conceptual model's depiction of an effective preschool PA-promoting environment. Results suggest that a single component of the original four-component conceptual model, providing opportunities for moderate-to-vigorous physical activity through recess for 4-year-old children in preschool settings, may be a good starting place for increasing moderate-to-vigorous physical activity. Interventions that are implemented with optimal levels of completeness and fidelity are more likely to achieve behavior change if they are based on accurate conceptual models. Examining the mechanisms through which an intervention produces its effects, as articulated in the conceptual model that guides it, is particularly important for environmentally focused interventions because they are guided by emerging frameworks. The results of this study underscore the utility of using implementation monitoring data to examine the conceptual model on which the intervention is based.